Study of surgical outcome of mid third clavicle fractures surgically managed by locking compression plate - Rani, Potharaju Swetha; Vasif, M. Zeeshan (International Journal of Research in Orthopaedics, 2021)
Clavicle is one of the most frequently fractured bones in young and active individuals. They account for 2.6-12% of all fractures and for 44-66% of fractures around the shoulder. Majority of clavicle fractures are mid shaft (80-85%). Functional outcome of midshaft fracture not only depends on the union but also on its length which has to be maintained. Thus a displaced or comminuted fracture carries a risk of symptomatic malunion, non-union or poor functional outcome with cosmetic deformity. The recent trend is shifting to internal fixation of these displaced mid shaft clavicle fracture. This was a prospective study of 20 cases of fresh mid third clavicle fracture admitted to MNR medical college and hospital from August 2020 to September 2021. Cases were taken according to inclusion and exclusion criteria. Medically unsuitable and patients not willing for surgery were excluded from the study. There were 17 male patients and 3 female patients with mid 1/3 closed clavicle fracture. 12 patients had right sided clavicle fracture and 8 patients had fracture of the left clavicle. All 20 fractures were closed fractures. Majority of the patients sustained fracture due to road traffic accident (high energy trauma) in 16 cases, fall from height in 3 cases and assault in one case. The mean duration to surgery from the day of presentation and injury was 2.1 days for middle third clavicle fractures. Functional outcome as assessed by constant and Murley scoring was favourable with excellent to good result in 97% cases and fair in 3% cases. The average constant score was 93.35 in one year follow up in middle third group. This study has some limitations. The conclusions drawn from this analysis cannot be generalized because of the small number of cases. In conclusion, for middle third clavicle fractures bony union could be achieved with locking compression plates and the clinical outcomes were satisfactory. All the fractures united and there were no cases of nonunion.